1993
DOI: 10.1142/9789812797919_0047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traffic Scenes by Using the Hierarchical Structure Code

Abstract: Object recognition in natural surroundings is one of the most ambitious goals of digital image processing. In our work, strategies for the analysis of traffic scenes are investigated. The Hierarchical Structure Code (HSC) is applied to this problem and it has been shown that fast object recognition is possible. The HSC provides a unified approach for contour-based and region-based descriptions of structures. Hardware is being built to compute the HSC in video real time and a library of HSC-operations has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Experiments showed that a robust recognition of traffic signs is possible up to a distance of 30 meters using our equipment. Detailed recognition results can be found in [2]. After parallelizing the algorithms When analyzing the runtime, some points have to be considered:…”
Section: Resultsmentioning
confidence: 99%
“…Experiments showed that a robust recognition of traffic signs is possible up to a distance of 30 meters using our equipment. Detailed recognition results can be found in [2]. After parallelizing the algorithms When analyzing the runtime, some points have to be considered:…”
Section: Resultsmentioning
confidence: 99%
“…Among those who work directly with a black and white image are Austerirmeier et al [5], Besserer et al [8] and Buker and Mertsching [10] who detect the borders in a pyramidal structure. They do not take occlusions into account.…”
Section: Sign Detectionmentioning
confidence: 99%
“…However there are some researchers who prefer not to use it. In those implementations where grayscale images are preferred, the TRD is based mainly on morphology features, such as symmetry [54], [55], [56], distance transformations from offline generated templates [57] and pyramidal structures for border detection [58], [59], [60]. A machine learning approach to TSR using genetic algorithms and neural networks is proposed in [61].…”
Section: Related Workmentioning
confidence: 99%